2016
DOI: 10.1016/j.addr.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Progress and problems with the use of suicide genes for targeted cancer therapy

Abstract: Among various gene therapy methods for cancer, suicide gene therapy attracts a special attention because it allows selective conversion of non-toxic compounds into cytotoxic drugs inside cancer cells. As a result, therapeutic index can be increased significantly by introducing high concentrations of cytotoxic molecules to the tumor environment while minimizing impact on normal tissues. Despite significant success at the preclinical level, no cancer suicide gene therapy protocol has delivered the desirable clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
168
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(178 citation statements)
references
References 160 publications
(168 reference statements)
0
168
1
5
Order By: Relevance
“…Suicide genes are still an important tool for in vivo safety control in adoptive cellular immunotherapy with autologous or allogeneic T-cells genetically modified with chimeric antigen receptors or affinity-enhanced T-cell receptor chains (reviewed in Karjoo et al (2016)). The concept of using the human CYB4B1 as a suicide gene was developed by Wiek et al (2015) who showed that the exchange p.S427P (h-P427) is important for both protein stability as well as partially rescuing the catalytic activity of the human enzyme against 4-IPO 12.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide genes are still an important tool for in vivo safety control in adoptive cellular immunotherapy with autologous or allogeneic T-cells genetically modified with chimeric antigen receptors or affinity-enhanced T-cell receptor chains (reviewed in Karjoo et al (2016)). The concept of using the human CYB4B1 as a suicide gene was developed by Wiek et al (2015) who showed that the exchange p.S427P (h-P427) is important for both protein stability as well as partially rescuing the catalytic activity of the human enzyme against 4-IPO 12.…”
Section: Introductionmentioning
confidence: 99%
“…Tested drugs included MMAE (microtubule‐disrupting agent),12, 13 SN‐38 (topoisomerase I inhibitor),14 etoposide (topoisomerase II inhibitor),15 cisplatin (DNA crosslinker),16 6‐MP (nucleotide analogue and inhibitor of RNA and protein synthesis)17, 18 and 5‐FU (pyrimidine analogue and thymidine synthase inhibitor) 18, 19. As we mentioned above, OVASC‐1 cells have been shown to be resistant to paclitaxel; therefore, we did not examine their sensitivity to this drug at the in vitro level to avoid redundancy.…”
Section: Resultsmentioning
confidence: 99%
“…While past clinical trials with CD/5-FC system alone have reported limited success (Karjoo et al 2016), there are several new clinical trials in progress which could produce interesting outcomes. For instance in one trial, genetically-modified neural stem cells expressing bCD are used in combination with orally administered 5-FC for the treatment of recurrent gliomas (NCT01172964).…”
Section: Enzyme/prodrug Systemsmentioning
confidence: 99%